Impact of onset-to-door time on outcomes and factors associated with late hospital arrival in patients with acute ischemic stroke. - Eung-Joon Lee; Seung Jae Kim; Jeonghoon Bae; Eun Ji Lee; Oh Deog Kwon; Han-Yeong Jeong; Yongsung Kim; Hae-Bong Jeong (PLoS ONE)
Background and purpose Previous studies have reported that early hospital arrival improves clinical outcomes in patients with acute ischemic stroke; however, whether early arrival is associated with favorable outcomes regardless of reperfusion therapy and the type of stroke onset time is unclear. Thus, we investigated the impact of onset-to-door time on outcomes and evaluated the predictors of pre-hospital delay after ischemic stroke. Methods Consecutive acute ischemic stroke patients who arrived at the hospital within five days of onset from September 2019 to May 2020 were selected from the prospective stroke registries of Seoul National University Hospital and Chung-Ang University Hospital of Seoul, Korea. Patients were divided into early (onset-to-door time, ≤4.5 h) and late (>4.5 h) arrivers. Multivariate analyses were performed to assess the effect of early arrival on clinical outcomes and predictors of late arrival. Results Among the 539 patients, 28.4% arrived early and 71.6% arrived late. Early hospital arrival was significantly associated with favorable outcomes (three-month modified Rankin Scale [mRS]: 0-2, adjusted odds ratio [aOR]: 2.03, 95% confidence interval: [CI] 1.04-3.96) regardless of various confounders, including receiving reperfusion therapy and type of stroke onset time. Furthermore, a lower initial National Institute of Health Stroke Scale (NIHSS) score (aOR: 0.94, 95% CI: 0.90-0.97), greater pre-stroke mRS score (aOR: 1.58, 95% CI: 1.18-2.13), female sex (aOR: 1.71, 95% CI: 1.14-2.58), unclear onset time, and ≤6 years of schooling (aOR: 1.76, 95% CI: 1.03-3.00 compared to >12 years of schooling) were independent predictors of late arrival. Conclusions Thus, the onset-to-door time of≤4.5 h is crucial for better clinical outcome, and lower NIHSS score, greater pre-stroke mRS score, female sex, unclear onset times, and ≤6 years of schooling were independent predictors of late arrival. Therefore, educating about the importance of early hospital arrival after acute ischemic stroke should be emphasized. More strategic efforts are needed to reduce the prehospital delay by understanding the predictors of late arrival.